Nosso modo de vida vale a pena: um estudo sobre pescadores artesanais maranhenses - Moler, Lais Biasoli (2011)
The present study seeks to investigate and analyze, from the Social-Historical Psychology viewpoint, the psychosocial effects brought about by the prevalent social and economic system to human groups through a study case contemplating a group of traditional fishermen in the city of São Luís, in Maranhão, whose fishing activities in the beach area called Praia do Boqueirão seem to be menaced by construction works being developed around the Complexo Portuário Ponta da Madeira by the transnational company Vale. The methodology is based on the participant-observation and action-research strategies, which seek to contextualize the subjects according to social, economic, historical and cultural factors in order to properly recognize and appreciate their values and cultural aspects as well as to promote the debate and free expression. The data analysis indicates that social and environmental interventions resulting from economic system pressures transcend the realm of climate changes disseminating throughout social relations and altering objectivities and subjectivities, establishing a new logic given by the dialectics of inclusion-exclusion which, ultimately, ends up by changing a group s social subjectivity